EVALUASI PENDIDIKAN ISLAM DI ERA KONTEMPORER: KONSEP, PRINSIP, METODE, DAN IMPLEMENTASI - Kuncoro, Achmad Isro' Kuncoro; Maryono, Maryono (Universitas Nahdlatul Ulama Surakarta, 2025)
The evaluation process within Islamic education holds a crucial role, functioning not only as a tool to measure students’ academic achievements but also as an instrument to assess their moral, spiritual, and behavioral competencies. As Islamic education aims to develop comprehensive individuals characterized by faith, knowledge, and noble character, evaluation should align with these multidimensional goals. This study aims to elaborate the concepts, guiding principles, evaluation methods, and implementation strategies of educational evaluation in Islamic education, particularly in the context of contemporary challenges. Employing a descriptive qualitative research method through extensive literature review from national and international academic sources within the last five years, this article identifies various techniques applied in Islamic educational settings, ranging from traditional oral and written tests to modern digital-based assessments. The findings highlight that evaluation in Islamic education should be based on Islamic values derived from the Qur'an and Hadith, while also embracing technological innovations. Moreover, the study underscores the importance of implementing a holistic and integrative evaluation system that measures cognitive abilities, moral character, spiritual development, and social skills. This study emphasizes the importance of implementing a holistic evaluation system that includes assessments of students’ cognitive abilities, moral character, spirituality, and social skills. This necessity arises from the fact that evaluation systems commonly applied in many Islamic educational institutions still predominantly focus on cognitive achievements, while moral and spiritual aspects are often overlooked. In reality, the challenges of contemporary Islamic education, especially in the digital era, are not limited to academic mastery but are closely related to moral degradation, value disorientation, and the negative influence of instant digital culture on student behavior. Therefore, this article proposes an integrative evaluation model based on Islamic values, which is not only relevant to be applied in the digital era but also essential as a strategic solution for establishing a comprehensive, fair, and technology-adaptive evaluation system for Islamic education that remains grounded in Sharia principles. This model is expected to serve as a reference for Islamic educational institutions in designing a more holistic, balanced, and contextually appropriate evaluation framework in line with the needs of contemporary Islamic education.